Surface plasmon polariton interaction with Sulforhodamine 101 dye - Baieva, Svitlana (2011)
The integration of conventional optical elements and electronic circuits is limited by size mismatch between these components. The diffraction limit does not allow miniaturizing optical elements to nm-scale. It was realized that light being strongly coupled to coherently oscillating electrons at the metal surface could be used to overcome this limit. The coupled state is called surface plasmon polariton. Surface plasmon polariton propagates in plane of metallic film within 10-100 μm range but decay exponentially in perpendicular directions to metal-dielectric boundary. Interaction of the surface plasmon polaritons with fluorescent dye molecules may result in development of new nanodimensional photonic elements as planar frequency converters, planar refractive elements with desirable refractive index etc. Conversion from light to the surface plasmon polariton modes and backwards can be done employing fluorescent molecules. Due to imperfections of metallic film surface plasmon polariton can be scattered into photons that can excite fluorescent molecules. One of the most powerful techniques of the surface plasmon polaritons propagation imaging is based on this effect. The study of surface plasmon polaritons interaction with fluorescent dye molecules is high priority task. The aim of this thesis is an investigation of the interaction between surface plasmon polaritons and Sulforhodamine 101 dye molecules. The fundamental property of SPP oscillation is dispersion relation: the dependence of energy of oscillation on the wave vector of the oscillation. The dispersion curves for silver-Sulforhodamine 101 samples are obtained experimentally performing reflectometry measurements. Excitation is done by using prism coupling technique (Kretschmann configuration). The vacuum Rabi splitting is observed. Transfer matrix method is used to model reflection coefficient R of studied multilayer structures. Detection of the scattered radiation provides another way to get dispersion relation of surface plasmon polaritons. Comparison of this dispersion relation to one obtained from reflectometry measurements provides insight into dynamics of surface plasmon polariton/dye molecules interaction.